90 The impact of apprenticeships on the workforce. (15th December 2021) - Moise, Shakira; Manget, Jesse; Parry, Loren; Porter, Lauren; Knight, Alice; Paul, Clare; O'Sullivan-Whiting, Laurence
Abstract : Background: GOSH has over 200 Apprentices across 35 different clinical and non-clinical apprenticeships. In line with the GOSH Learning Academy priorities and the GOSH people strategy; opportunities for progression, retention and diversity were increased through the expansion of apprenticeship programmes. Methods: Initially focusing on data for the Healthcare support worker (HCSW) apprenticeship. Recruitment carried out through partnerships with local businesses, schools and community helped the trust reflect the people it serves, developing a diverse workforce. Data from this group was anonymised and compared with employees on a former non-apprenticeship pathway (University Certificate of Competence (UCC)) ethical approval was not required. Data was analysed for learner retention, current roles and further progression through other apprenticeship routes. Further analysis was then undertaken of data from all GOSH apprenticeships to compare this with National Statistics. The data analysed included the percentage of apprentice's vs total trust workforce, and percentage of BAME apprentices. Results: The HCSW apprenticeship has demonstrated a significant increase in staff retention at 95% vs 51% when compared to the UCC. A full salary support provided by the GOSH children's charity has enabled 25% to progress onto nursing apprenticeships. By investing in our local community and promoting diversity we have over 50% BAME enrolment onto Apprenticeships. Over 4 years we have averaged 2.3% of our workforce on an apprenticeship, meeting the public sector target. Discussion: Dedicated educators have worked to provide high quality training equipping apprentices with the knowledge, skills and behaviours to provide exceptional care to patients at GOSH. Apprenticeships create access to pathways which were previously only open to university graduates. Retaining learners leads to the ability to create lifelong learning maximising the advantages a diverse workforce brings. Conclusion: We have demonstrated that apprenticeship pathways offered by GOSH have a positive and significant impact on retention, inclusion and progression.